Simulation of Heat Transfer Rate in Motorcycle Engine Cylinder with Variation of Distance Between Fins and Material - Zainal, Mohamad Zainal Abidin; Sugeng Hadi Susilo (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Cylinder blocks on motorcycles that do not use a radiator cooling mechanism generally use a fin mechanism around the motorcycle cylinder block. Fins on motorcycles are useful for spreading the heat from combustion from the inside out, so that the engine temperature does not heat up quickly. During the combustion process in the cylinder block can cause heat with a high temperature. If this heat is not immediately distributed around it will cause excessive heat and will cause over heating on the motorcycle, which can interfere with the performance of the motorcycle. Thermal analysis is often used to study heat transfer on many surfaces including fins, cylinder block of an internal combustion engine and also the material of the mold block. The engine cylinder with fins was designed using Autodesk Fusion 360 with different spacing between fins of 10 mm, 8 mm, 6 mm and 4 mm. The materials used for modeling in this study are Al 356 (cast alloy), AA 2014T6 (Wrought alloy), AA 1060 (Wrought alloy), cast iron with 2% nickel, AM60A-F (Cast alloy), Magnesium alloy (AZ63A), Aluminum 6061, Gray cast iron grade 20, Al 360 (cast alloy), Al 380 (cast alloy). The simulation results of the engine cylinder block made of cast iron with 2% nickel with fins having a spacing between fins of 4 mm and a cylinder perforation diameter of 4 mm on the fins are most suitable for a better heat transfer rate compared to the other materials used in this study